1984
DOI: 10.1111/j.1464-5491.1984.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer and Diabetes Mellitus

Abstract: In a series of 6,500 patients with diabetes mellitus there were 37 cases of primary carcinoma of the pancreas which significantly exceeded the expected number for the patient years at risk in both males and females (p less than 0.01). There was no evidence that pancreatic cancer was more common in patients with long-standing diabetes. The increased incidence of pancreatic cancer in diabetic patients is probably the result of patients presenting with the symptoms of diabetes as long as four years before the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The current estimation of the overall risk of pancreatic cancer among diabetics is consistent with the up to 2-fold increase in risk reported by other investigators (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and supports previous work that has identified an inverse temporal relationship between diabetes and pancreatic cancer with cancer-associated risk decreasing with increasing duration of diabetes (5, 13, 16, 29-32) Because of rapid case ascertainment, use of in-person interviews rather than proxy, and population-based sampling, our observations are robust and lend further support to the hypothesis that diabetes may often be a consequence rather than a cause of pancreatic cancer, or an early marker of the disease (6, 10, 16, 20-23, 33, 34). Our results extend the results of prior case-control and cohort studies by assessing the association between medication use for diabetes and pancreatic cancer risk.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The current estimation of the overall risk of pancreatic cancer among diabetics is consistent with the up to 2-fold increase in risk reported by other investigators (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and supports previous work that has identified an inverse temporal relationship between diabetes and pancreatic cancer with cancer-associated risk decreasing with increasing duration of diabetes (5, 13, 16, 29-32) Because of rapid case ascertainment, use of in-person interviews rather than proxy, and population-based sampling, our observations are robust and lend further support to the hypothesis that diabetes may often be a consequence rather than a cause of pancreatic cancer, or an early marker of the disease (6, 10, 16, 20-23, 33, 34). Our results extend the results of prior case-control and cohort studies by assessing the association between medication use for diabetes and pancreatic cancer risk.…”
Section: Discussionsupporting
confidence: 77%
“…Case-control studies show that patients with pancreatic cancer have an increased risk for new diagnoses of diabetes, especially within 3 years before their cancer diagnosis (6,23). Other cohort studies have reported an association between new-onset diabetes and cancer, but conclusions about the strength of this association are limited by the small number of incident cases of pancreatic cancer in cohort studies (21)(22)(23).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Everhart and Wright [75] conducted a meta-analysis of 20 studies and concluded that the relative risk for pancreatic cancer in people diagnosed with diabetes at least 5 years prior to pancreatic cancer was 2.0. However, a number of other studies have reported that diabetes does not increase the risk of pancreatic cancer [69,[76][77][78]. Morris and Nabarro [76] found no evidence that pancreatic cancer was more common in patients with diabetes of 3 or more years' duration in their study of a series of 6,500 patients with diabetes mellitus.…”
Section: Diabetes and Pancreatic Cancermentioning
confidence: 78%
“…However, a number of other studies have reported that diabetes does not increase the risk of pancreatic cancer [69,[76][77][78]. Morris and Nabarro [76] found no evidence that pancreatic cancer was more common in patients with diabetes of 3 or more years' duration in their study of a series of 6,500 patients with diabetes mellitus. Gullo et al [69] conducted a multicenter study with 720 pancreatic cancer patients and 720 control patients concluded that diabetes is not a risk factor for pancreatic cancer.…”
Section: Diabetes and Pancreatic Cancermentioning
confidence: 78%